MULTI-STAGE TECHNICAL AND BIOENGINEERING RECLAMATION OF ERODED SKID TRAILS IN THE MOUNTAIN FORESTS OF THE UKRAINIAN CARPATHIANS - Bakay, Borys; Sishchuk, Mariana; Kuzyk, Pavlo; Цимбалюк, Yuri (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The paper substantiates the necessity of integrated technical and bioengineering reclamation for stabilizing eroded skid trails in the mountain forests of the Ukrainian Carpathians. Long-term operation of skid trails without proper maintenance leads to the transformation of ruts into deep gullies and ravines, removing 50 to 200 m³ of soil per kilometer of trail per season. Based on field research, classifications of erosion disturbances and damage degrees have been developed. The methodology of technical measures (deep ripping to 60 cm, convex cross‑section shaping, drainage structures, mulching) and bioengineering structures (live stakes, fascines, brush layers) is described in detail. Field testing results showed cutting survival of 78%, a 12‑fold reduction in soil loss, and soil density stabilization at 1.28-1.35 g/cm³. Adherence to the proposed algorithm reduces the restoration period from several decades to 5-7 years.